Enhancing the operational flexibility of thermal power plants by coupling high-temperature power-to-gas. (1st April 2020) - Sun, Yang; Wang, Ligang; Xu, Cheng; Van herle, Jan; Maréchal, François; Yang, Yongping
Highlights: Power-to-gas coupled with coal power plants for renewable power accommodation. Flexibility of coal power plant enhanced while storing excess renewable power in hydrogen. Minimum load rate of coal power plant significantly reduced by 18% points. A limited penalty on power generation efficiency caused by the coupling. Optimal operating strategies identified considering efficiency and CO2 emission. Abstract: The increasing penetration of intermittent renewable power challenges the stability of the electrical grid, thus coal power plants are usually required to extend the operation range by reducing the minimum load. This work proposes a concept of coupling solid-oxide cell stack based power-to-gas with coal power plants to allow for dual functions of (1) storing excess renewable electricity and (2) reducing the minimum load of coal power plants by combustion stabilization with oxygen-rich air from power-to-gas. The performance and operating strategy of such an integrated plant are evaluated with detailed off-design characteristics of the considered coal power plants. The results show that the integration of power-to-gas affects the distribution of the heat absorbed by radiative and convective heat exchangers in the boiler, stabilizes coal combustion, and reduces the superheat degree of live/reheated steam. It allows the power plant for operating at a significantly low load of down to 22% of the nominal load, compared with 40% before the coupling; meanwhile, a very limited penalty is caused with the plant efficiency reduced from 34.4% down to 34.1% (with 13% of the normalized power-to-gas capacity). Minimizing the power-to-gas contribution to the accommodated renewable power is advantageous for a minimal CO2 emission; nevertheless, maximizing the power-to-gas contribution with the coal power plant at high load allows for a maximal system efficiency.